2013
DOI: 10.1007/s00586-013-2893-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics a cure for back pain, a false dawn or a new era?

Abstract: The recent publication in this journal of papers by Albert and colleagues [1,2] from Denmark suggesting that low grade anaerobic bacterial infection may be the underlying cause of significant persistent chronic back pain in a welldefined group of patients has precipitated an unprecedented response in the medical and lay media. In the midst of claim and counterclaim, these studies represent a significant and substantial change in our understanding of the pathophysiology of back pain in some patient groups, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A recent study has suggested antibiotic treatment as an effective option for a specific subgroup of patients with Modic type 1 changes [9]. Significant controversy has followed, with a number of authors raising concerns about the methodology and conclusion of that study [41][42][43][44][45][46][47][48][49][50][51][52]. Within the restrictions of our specimen size, and our study being a bone micro-architecture and remodelling study, not aimed at investigating bacterial infection, our histological slides of the bone biopsies (H&E stained) did not show associated oedema and no cellular infiltrate to indicate overt inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has suggested antibiotic treatment as an effective option for a specific subgroup of patients with Modic type 1 changes [9]. Significant controversy has followed, with a number of authors raising concerns about the methodology and conclusion of that study [41][42][43][44][45][46][47][48][49][50][51][52]. Within the restrictions of our specimen size, and our study being a bone micro-architecture and remodelling study, not aimed at investigating bacterial infection, our histological slides of the bone biopsies (H&E stained) did not show associated oedema and no cellular infiltrate to indicate overt inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the material analysed in the present study included bone biopsies only, and not intervertebral disc which may contain bacteria and show inflammation. This remains a controversial topic, in need of further research as suggested by numerous letters to this journal [41][42][43][44][45][46][47][48][49][50][51][52]. Hence, evidence supporting the biomechanical and biochemical hypotheses is still not sufficient, and it remains unclear how they may play a synergistic role in the development of Modic changes in the human body [3].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there has been controversies and argumentation against the relationship between bacteria and Modic changes, highlighting that the isolated P. acnes was the contamination during tissue harvest rather than the original colonization inside intervertebral discs [ 12 ]. In addition, the lack of deterministic causal evidence based on animal studies was another major defect [ 13 ]. To solve this problem, Koch's Postulates, which demonstrate that pathogenic microbes isolated from patients could cause the same disease in animal models, were a reasonable method [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that in this very specific group of chronic low back pain, antibiotic treatment is effective. As one might expect this startling development (reminiscent of the discovery that peptic ulcer was due to helicobacter infection has led to considerable discussion [14][15][16] and even two editorials [8]). The paper by O'Dowd and Casey [16] deserves careful reading, emphasising not only the important significance of these papers, but also the fact that these are a small group of patients, not representative of a large population of patients with chronic low back pain.…”
Section: Back Painmentioning
confidence: 99%